Organization of Cost Accounting in State Higher Education Institutions (The Peerian Journal, 2023)
The article examines drastic changes related to the granting of financial independence in higher education institutions, as well as ways to create an environment of independence in other areas. Reforms carried out in the state higher education institutions, formation and analysis of another new system were carried out and conclusions were presented